Restoring Tourism in Serbia: the Role Played by Volunteering in Vojvodina - Klićek, Tamara; Breda, Zélia (Turyzm/Tourism, 2008)
The Instability caused by civil unrest and the wars for independence led some post-socialist countries in South-eastern Europe to lag behind in socio-economic development. One of the affected countries was Serbia which experienced economic stagnation and a halt in tourist activities as a result of the unrest of the 1990s. Serbia is now trying to gain a position in international tourism and is undertaking serious efforts to improve tourism in four key clusters. One of these is Vojvodina, where numerous volunteer tourism activities have been promoted providing socio-economic development in local communities. This paper discusses the importance of volunteering as a strategy for developing tourism in a Serbia which is still suffering economically and socially from damage caused by war. It presents the state of tourism in Serbia and outlines the situation in Vojvodina. Furthermore, through the case study of the Volunteer Centre of Vojvodina, the paper addresses how volunteering activities can contribute to tourism development.